Una forma diferente, aparentemente nueva, basada en la programación neurolongûistica (PNL), de enseñar histología bucal a estudiantes de pregrado en la Facultad de Odontología de la Universidad de Antioquia, Medellín, Colombia - Jiménez Gómez, Raúl (Revista Facultad de Odontología Universidad de Antioquia, 2009)
University teaching in Basic Sciences such as Oral Histology, has been traditionally done by means of lectures and microscopic practices that do not seem to be the best method in today´s world. Neurolinguistic Programming (NLP) is a new epistemology that allow us to learn how people learn and how to teach them. A methodology based on NLP, was applied to five consecutive groups of undergraduate students of the Dental School of the University of Antioquia, Medellin, Colombia. Four hours per week during six weeks were used. NLP tests were done in order to find out how they learned; they were asked to study the subject previously at home, to draw the microscopic structure of the oral tissues with colors, as well as the elaboration of mental maps. This was done to stimulate creativity, original work and capacity for synthesis. An initial evaluation was done in the classroom, and then, an oral and written presentation, by at least five of the students and for a period of five to ten minutes. The most important points were complemented and emphasized by the teacher. The oriented students answered all their doubts. At the end a final evaluation was done. The students excellence was praised an encouragement was given. After five courses, this appears as a good way to teach a basic science such as Oral Histology.